Destination service quality, tourist satisfaction and revisit intention: the moderating role of income and occupation of tourist / Kamaleswar Boro - Boro, Kamaleswar (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The purpose of this study is to understand tourist revisit intention by knowing their level of satisfaction in terms of different SERVQUAL dimensions. Recent studies on tourism have explored several service quality dimensions to know customer satisfaction and revisit intention. However, there has been lack of studies examining the moderating role of income and occupation on the relationship between customer's satisfaction and revisit intention. Therefore, the present study intends to fulfill this gap. The research design is descriptive and analytical in nature. SERVQUAL dimensions have been used for this study. Data was collected from 160 respondent tourist visiting Meghalaya, a popular destination for tourist in North East India. Structured Equation Modeling was used to analyze the data. The findings suggest a significant relationship in terms of SERVQUAL attributes with customer's satisfaction as well as revisit intention. SERVQUAL dimensions are crucial attributes for tourist satisfaction which in turn has an impact on revisit intention. To plan for a revisit, tourist must be first and foremost satisfied with the destination image and facilities available. The findings also show the moderating role of income on the relationship between customers' satisfaction and revisit intention. The study findings can be used by service provides in tourism industry to develop service quality dimensions which can deliver tourist satisfaction. The present study is unique as it explores the relationship of three conceptual frameworks namely; SERVQUAL dimensions, tourist satisfaction and revisit intention and also examines the moderating role of income and occupation on the relationship between tourist satisfaction and revisit intention.